The basics of filmmaking - Brown, Blain (2020)
"The Basics of Filmmaking is an introductory textbook tailored to the needs of beginning and intermediate film students and independent filmmakers that expertly guides you through the entirety of the craft, from screenwriting all the way through to editing, with details chapters covering each department involved in the filmmaking process. The book takes a behind-the-scenes look at every aspect of the filmmaking process: writing the screenplay (and getting it critiqued by a professional), pre-production, cinematography, lighting, the shooting process, getting good audio, editing, and even going to a pitch meeting to sell it. It addresses the real fundamentals, the mechanics and the basics concepts of how to write, produce, direct, shoot, record, and edit your movie. Written by Blain Brown, a seasoned expert who has worked professionally as a cinematographer, screenwriter, director, producer, line producer, assistant director, gaffer, grip, and editor, this is a must have resource for any filmmaking student. Featuring an accompanying companion website with video examples of scene directing methods, continuity and coverage, working with the camera, lighting, audio, and editing and downloadable production forms you can fill out and use for your projects"--
Filmmaking : the basics -- Writing your story -- Production -- The ad team -- Continuity and coverage -- The work of the director -- Cinematography -- Lighting and grip -- The art department -- Slating and scripty -- Audio basics -- The work of the editor -- Safety -- Getting started in the business.
Includes bibliographical references (pages 161-168) and index.
Keywords: Motion pictures -- Production and direction